Multi-center randomized superiority clinical trial in the early phase of mechanically ventilated patients to preserve diaphragm thickness using non-invasive magnetic phrenic nerve stimulation: STIMIT ACTIVATOR 1 pivotal trial - Annia F. Schreiber; Carles Subirà; Michael Sklar; Marlene Santos; Matthew Ko; Alessandro Panelli; Stefan J. Schaller; Danny Theodore; Daniel D. Rowley; David Watson; Pramod Bonde; Elias N. Baedorf Kassis; et al. (Trials, 2025)
Abstract Background Ventilator-induced diaphragmatic dysfunction (VIDD) occurs in up to 60% of mechanically ventilated patients and prolongs ventilatory dependance. The consequences of VIDD are muscle atrophy, reduction of strength, and injury of muscle fibers. Atrophy and contractile activity of the diaphragm can be estimated by ultrasound muscle thickness and thickening fraction. Prior experience demonstrates invasive electrical stimulation of the diaphragm helps preserve muscle thickness. This is the first study on a non-invasive phrenic nerve stimulator that aims to assess its feasibility, safety, and usefulness in preserving diaphragm thickness. Methods A multi-center randomized clinical trial will be performed in four intensive care units (ICUs) in the United States of America and Canada. Inclusion criteria include patients older than 21 years, in the first 48 h of mechanical ventilation (MV) and predicted to remain on the ventilator for at least 48 h. Patients with contraindications for phrenic nerve stimulation, severe chronic pulmonary diseases, or impossibility to measure diaphragm thickness with ultrasound will be excluded. Patients enrolled will be randomized to standard care (control) or 30-min daily non-invasive phrenic nerve stimulation up to 10 days after enrollment (intervention). The primary effectiveness endpoint is the change in diaphragm thickness on day 10, extubation, or death whichever occurs first. Secondary endpoints include change in diaphragm thickness on day 4, maximal inspiratory pressure before extubation, and time-to rapid shallow breathing index (RSBI) <105. Safety objectives include the proportion of device- or procedure-related adverse events (SAE). The estimated sample size will be 40 patients (20 per group). Discussion The STIMIT ACTIVATOR trial is a randomized multi-center study powered to elucidate whether non-invasive phrenic nerve stimulation is feasible, safe, and preserves diaphragm thickness. Meeting the primary endpoint will demonstrate its applicability in clinical practice to prevent diaphragmatic atrophy in ventilated patients. Trial registration ClinicalTrials.gov: NCT05883163, August 29, 2023.